Demand and Training Pathways for “Chinese + Vocational” Talent in Indonesia: Trends and Development Strategies - Julianti Julianti; Zhang Hao (Jurnal Pendidikan Indonesia, 2025)
This study explores the demand for "Chinese + Vocational" talents in Indonesia and the pathways for their cultivation. Using a mixed-methods approach that combines surveys and interviews, the findings reveal a significant need for such talents, particularly in trade, tourism, and artificial intelligence industries. Grounded in Gardner's social-educational model and Dornyei's second-language motivation self-system, the study highlights the critical role of learner motivation. Notably, 61.9% of respondents cited career advancement as their primary reason for learning Chinese, emphasizing the strong link between language acquisition and professional aspirations. Despite this demand, the current "Chinese + Vocational" curriculum faces significant challenges, including rigid structures, a shortage of qualified instructors, and limited teaching resources. Moreover, 79.7% of Indonesian learners have only intermediate or lower Chinese proficiency, limiting their ability to use the language in professional settings. To effectively address these challenges, this study recommends aligning curricula with market needs, strengthening faculty development, integrating diverse teaching resources, and enhancing school-enterprise collaborations. These findings offer valuable insights into implementing "Chinese + Vocational" education in Indonesia and have broader implications for international Chinese language education. The study underscores the importance of continuous adaptation, strategic refinement in talent cultivation, and global academic collaboration.